The Future of the Humanities in Today's Financial Markets. Issue 3 (June 2014) - Lea, David
Abstract In this essay David Lea approaches the decline in the study and teaching of the humanities within the university context from a financial perspective. As humanities departments are either closed down or have their curriculum attenuated, it is obvious that the revenue previously available to support such programs has not been forthcoming. This change is often explained as the result of cost cutting necessary during periods of financial crisis, but this justification is belied by the fact that while the humanities have suffered during recent "financial crises, " other areas within the university have grown. Resources that could have supported the humanities have instead been applied elsewhere: first, to increasing the administration and ancillary support staff; and second, in support of subjects oriented toward technology and the market. Ultimately, Lea links the decline of the humanities to the growing financialization of the economy, the ideology of managerialism, and a contemporary tradition that accords with the "procedures of the realms of the market and of liberal individualist politics."